Knowledge gaps and positive attitudes toward adult vaccination among nursing students: A Cross-sectional study - Noelia Rodríguez-Blanco; Nancy Vicente-Alcalde; Cristina Orts-Ruiz; Sergio Montero-Navarro; Cristina Salar-Andreu; Jesús Sánchez-Más; José Luis Duro-Torrijos (PLoS ONE, 2026)
Background Vaccination is one of the most effective public-health measures, yet adult coverage in Spain remains suboptimal due to misinformation and hesitancy. Nursing students, as future immunization promoters, play a pivotal role in vaccine recommendations. This study explored knowledge, attitudes, and recommendation practices regarding adult vaccination among undergraduate nursing students. Methods An observational, descriptive, cross-sectional study was conducted in the province of Alicante, Spain, between April and May 2025. An ad hoc electronic survey with 19 closed-ended items was distributed to students from the three universities offering the Nursing degree in this province; 562 students participated. Differences across academic years were analyzed using Pearson’s χ² test for categorical variables and the Kruskal-Wallis test for the continuous variable age (non-normally distributed). Results Overall, 39.1% of nursing students were unaware of the Spanish adult vaccination schedule with significant differences across academic years (55.7% in first-year vs. 27.2% in fourth-year students; p < 0.001). Only 44.1% reported sufficient training on vaccines. Attitudes toward adult vaccination were predominantly positive: 61.4% highly favorable, 62.5% highly effective, 66.7% supporting mandatory vaccination. Additionally, 65.5% would recommend all scheduled adult vaccines. However, 47.9% perceived resistance from other healthcare professionals when recommending vaccines (p < 0.001 for the increase across academic years). Conclusions Nursing students in Alicante exhibit positive attitudes toward adult vaccination, yet significant knowledge gaps regarding the Spanish adult vaccination schedule persist even in the final year. Targeted curricular reinforcement from the first academic year is warranted within these three institutions to strengthen their role as immunization promoters.